2011
DOI: 10.5664/jcsm.1186
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' Knowledge, Behavior, and Attitudes Regarding Healthy Sleep in Young Children

Abstract: Study Objectives: To examine sleep health knowledge and beliefs and their relationship to sleep practices in a community sample of caregivers of young children. Methods: A convenience sample of caregivers visiting a museum on one of 2 consecutive weekend days completed a brief parent-report survey on child sleep habits and parental basic sleep knowledge and beliefs and attitudes regarding sleep as a health behavior. Results: Of the 253 analyzable surveys (response rate 80%; mean age of index child 3.4 ± 2.0 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 19 publications
(20 reference statements)
5
58
2
2
Order By: Relevance
“…14 Knowledge about healthy sleep tends to be limited among parents, 16,2325 50% of whom believe snoring is healthy. 23 Ethnic and economic disparities are great. Among low-income, racial-ethnic minority 5- to -6-year-olds, 94% screen positive for sleep problems.…”
Section: Introductionmentioning
confidence: 99%
“…14 Knowledge about healthy sleep tends to be limited among parents, 16,2325 50% of whom believe snoring is healthy. 23 Ethnic and economic disparities are great. Among low-income, racial-ethnic minority 5- to -6-year-olds, 94% screen positive for sleep problems.…”
Section: Introductionmentioning
confidence: 99%
“…When parent-reported usual bedtimes, wake times and daily nap durations were used to estimate daily sleep duration in 253 American children aged 3 months to 12 years, it was found that a quarter did not reach the daily duration of sleep recommended by the National Sleep Foundation for their age (Owens, Jones, & Nash, 2011). Addressing our limited understanding of the causes of variation in child sleep duration is therefore of growing importance.…”
Section: Introductionmentioning
confidence: 99%
“…Most recommendations focus predominantly on children's nighttime sleep duration (Mindell et al, 2009), with lesser attention on associations between sleep hygiene and daytime sleep or combined daytime and nighttime sleep (Owens et al, 2011; Sadeh et al, 2009). Evidence is mixed regarding whether or not the composition of children's daily sleep, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations